The Design and Development of the Internet-Based System for Testing and Analyzing the Psychological and Physiological Responses During Creative Learning - Wang, Junhui (Frontiers in Psychology, 2022)
An Internet-based system for testing and analyzing psychological and physiological responses during creative learning was developed using virtual instruments based on microcomputer interfaces and network communication technologies. The system can be used to study and evaluate innovative learning processes and performance at the psychological and physiological levels. This paper presents the design, implementation and application of the system.